2002
DOI: 10.1023/a:1014272816454
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The use of PLA and PLGA for drug delivery needs substantially more circumspection. As, according to FDA standards. the potential hazards of peptide acylation products need to be assessed, our findings may have significant implications for products already on the market. Techniques to minimize the acylation reaction are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…This presence of multiple peaks on the chromatogram with 1 or 2 glycolic acid units each also revealed that octreotide has multiple acylation sites (23). Nucleophilic functional groups such as the primary amino groups present in the N-terminus and lysine residue have been shown to be the major targets for peptide acylation (17, 19, 30). The individual peaks, octreotide and octreotide degradated products in HPLC chromatogram were identified through LC-MS based on the retention times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This presence of multiple peaks on the chromatogram with 1 or 2 glycolic acid units each also revealed that octreotide has multiple acylation sites (23). Nucleophilic functional groups such as the primary amino groups present in the N-terminus and lysine residue have been shown to be the major targets for peptide acylation (17, 19, 30). The individual peaks, octreotide and octreotide degradated products in HPLC chromatogram were identified through LC-MS based on the retention times.…”
Section: Resultsmentioning
confidence: 99%
“…Porous microspheres allow for rapid release of acidic PLGA oligomers, which typically raises the microclimate pH within eroding microspheres (32). Since acylation has been shown to be accelerated by high concentrations of oligomers in solution, as well as by acidic conditions (19, 20), more porous microspheres were expected to slow down and suppress the acylation of octreotide. In addition, acylation in microspheres containing water-soluble divalent cationic salts might be prevented by reducing sorption of octreotide to PLGA (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of ethyl-2-mercapto-acetate from residual ethanol present in an excipient (sodium starch glycolate) and compounds related to a thermal stabilizer present in PVC packaging material has been reported recently [35]. The acylation of peptides by lactic acid and glycolic acid inside degrading microspheres of poly(lactic acid) and poly(lacticco-glycolic acid) has also been observed [36]. Methylparaben (methyl p-hydroxybenzoate), used widely as an anti-microbial preservative, has been shown to undergo transesterification reactions with aldoses and alditols which are common excipients in pharmaceuticals [37].…”
Section: Resultsmentioning
confidence: 91%
“…4 Among these, p(HEMA) is one type of poly(α-hydroxy ethyl methacrylate) approved by U.S. Food and Drug Administration for clinical use. 5 It has proved to be a good candidate in the biomaterial field because of its high biocompatibility, 6, 7 nontoxicity, 8 better oxygen permeability, 9 and good transmission and absorption characteristics. 10 It has remarkable tolerance to entrapped cells and exhibits good chemical and hydrolyte stability.…”
Section: Introductionmentioning
confidence: 99%